EVALUASI PROGRAM PEMBERDAYAAN PETAMBAK PADA BUDIDAYA UDANG VANNAMEI OLEH PT INFISHTA DI KECAMATAN BLANAKAN KABUPATEN SUBANG - Amrial, Yudhi; Rahayu, Ety (Jurnal Pembangunan Manusia, 2021)
Poverty is the main problem experienced by fish farmer in Indonesia. This happens because of the monopoly by middlemen. One solution to this problem is by empowering fish farmer. This study aims to evaluate fish farmer empowerment programs through vannamei shrimp farming conducted by PT Infishta in Blanakan District, Subang Regency. The qualitative approach and the type of formative evaluation research conducted with in-depth interviews with 8 informants who know about the implementation of fish farmer empowerment programs in the vannamei shrimp farming. The results of the research explain the input stages and the program implementation process. The input stage includes several aspects, namely the method of funding with sources of funds obtained from investors. The funding method uses a peer-to-peer (P2P) lending system with an agreed profit. The human resources in the vannamei shrimp farming program consist of the Founder of Infishta as the person in charge of all fishery business activities and the Mina Ceria team as the implementing partner of the shrimp farming program. The beneficiaries of this program are fish farmer who are referred to as hatchlings, have commitment, and skills in shrimp farming. The process stage includes the preparation aspect by determining operational steps, introducing the program, instructions, and holding meetings. Implementation aspects include direction, shrimp seed stocking and maintenance, harvesting, monitoring, and reporting. Furthermore, the marketing aspect is carried out by semi auction to shrimp buyers.